2021
DOI: 10.1021/acsenergylett.1c01619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Electrically Driven Cholesteric Liquid Crystals by Triboelectrification and Their Application in Self-Powered Information Securing and Vision Correcting

Abstract: Smart glass technology is rapidly evolving and finding significant application in light selectivity devices. However, a major disadvantage of such devices is their high energy requirement which hinders the commercialization progress. In this work, a self-powered optical switch is developed based on the electrochromic effect induced by a vertical contact-separation triboelectric nanogenerator (VCS-TENG) in a cholesteric liquid crystal (CLC) display. The voltage produced by the VCS-TENG causes the CLC display to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Recently, the research group of Wang et al reported TENG-driven cholesteric liquid crystal devices and their application in information security, smart windows, optical switches, e-paper displays, and wireless sensors. To the best of the authors’ knowledge, these are the only four reports available in the literature on TENG-driven cholesteric liquid crystals. The present manuscript also reports a similar application using TENG-driven cholesteric liquid crystal devices but with additional advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the research group of Wang et al reported TENG-driven cholesteric liquid crystal devices and their application in information security, smart windows, optical switches, e-paper displays, and wireless sensors. To the best of the authors’ knowledge, these are the only four reports available in the literature on TENG-driven cholesteric liquid crystals. The present manuscript also reports a similar application using TENG-driven cholesteric liquid crystal devices but with additional advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al combined an optimized vertical contact-separation triboelectric nanogenerator (VCS-TENG) with the unique optical characteristics of the Ch-LCs to develop smart glasses (Figure 23d). [201] The VCS-TENG, which was fabricated by using a pair of triboelectric materials (polytetrafluoroethylene and chitosan/glycerol film), converted mechanical energy into an electrical signal to induce the rearrangement of Ch-LC molecules. The Ch-LCs were initially in the planar (P) state, leading to a partially transparent state.…”
Section: Mechanical Self-powered Lc-based Smart Windowsmentioning
confidence: 99%
“…[204] Copyright 2020, Wiley-VCH. Charging by RFS-TENG Wang et al [ 188] Energy-harvesting/conversion technologies and texture change of Ch-LCs VCS-TENG + Ch-LCs Transmittance ∼78% to ∼20% Charging by VCS-TENG Chen et al [ 201] Energy-harvesting/conversion technologies and texture change of Ch-LCs VCS-TENG + Ch-LC optical modulator…”
Section: Mechanical Self-powered Lc-based Smart Windowsmentioning
confidence: 99%
“…Cholesteric DOI: 10.1002/adom.202300296 liquid crystals (CLCs) exhibit structural colors due to their property of selectively reflecting light by means of a helical self-assembled structure in which the dielectric constant and refractive index are periodically arranged. These properties make them highly useful for dynamic display, [1][2][3] information storage, [4][5][6] and optical security applications. [7][8][9] Spherical CLCs particles are favored by researchers due to their angle-independent structural coloration.…”
Section: Introductionmentioning
confidence: 99%